The role of glucagon after bariatric/metabolic surgery: much more than an “anti-insulin” hormone - Gonzalo-Martín Pérez-Arana; Gonzalo-Martín Pérez-Arana; Alfredo Díaz-Gómez; José Bancalero-de los Reyes; Manuel Gracia-Romero; Antonio Ribelles-García; Francisco Visiedo; Francisco Visiedo; Álvaro González-Domínguez; David Almorza-Gomar; David Almorza-Gomar; José-Arturo Prada-Oliveira; et al. (Frontiers in Endocrinology, 2023)
The biological activity of glucagon has recently been proposed to both stimulate hepatic glucose production and also include a paradoxical insulinotropic effect, which could suggest a new role of glucagon in the pathophysiology type 2 diabetes mellitus (T2DM). An insulinotropic role of glucagon has been observed after bariatric/metabolic surgery that is mediated through the GLP-1 receptor on pancreatic beta cells. This effect appears to be modulated by other members of the proglucagon family, playing a key role in the beneficial effects and complications of bariatric/metabolic surgery. Glucagon serves a dual role after sleeve gastrectomy (SG) and Roux-en-Y gastric bypass (RYGB). In addition to maintaining blood glucose levels, glucagon exhibits an insulinotropic effect, suggesting that glucagon has a more complex function than simply an “anti-insulin hormone”.